Computational Propaganda In The 2024 Presidential Election Contestation Of The Republic Of Indonesia In The Diversion Of Public Opinion On Social Media - Arnus, Sri Hadijah; Hasrullah, Hasrullah; Cangara, Hafied; Sukri, Sukri (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
Computation propaganda which is aimed at diverting public opinion, is widely used in the world of politics in the current era of digital democracy. One of the effects of use computation propaganda namely the polarization of public opinion on social media. This needs to be a concern, especially in Indonesia which has a pluralistic society. This research wants to find out how computational propaganda strategies are used in the 2024 presidential election of the Republic of Indonesia. This research uses a qualitative descriptive method. The research data is the result of Social Network Analysis (SNA) on conversations about the 2024 presidential election which became a trending topic on Twitter/X social media. The analysis was carried out by Drone Emprit Academic, the data from the analysis was then interpreted by researchers. The results of the research show that the 02 Prabowo/Gibran candidate pair used a computational propaganda strategy in building and guiding public opinion about the pair. This can be seen on the SNA map where the sub-clusters are formed separately from the main cluster, creating a network mesh  network and post many to many This is a characteristic of a bot account. The narrative built by the network has a positive sentiment towards couple 02. The use of bots by one of the couples has the potential to create polarization of public opinion regarding the 2024 presidential election on social media. The use of computational propaganda has become unavoidable in today's rapidly developing technological era. Therefore, there is a need for understanding from an ethical perspective in using it and there is a need to increase political literacy and digital literacy for the community regarding this matter.